2022
DOI: 10.3390/plants11030394
|View full text |Cite
|
Sign up to set email alerts
|

The Photosynthetic Efficiency and Carbohydrates Responses of Six Edamame (Glycine max. L. Merrill) Cultivars under Drought Stress

Abstract: Vegetable-type soybean, also known as edamame, was recently introduced to South Africa. However, there is lack of information on its responses to drought. The aim of this study was to investigate the photosynthetic efficiency and carbohydrates responses of six edamame cultivars under drought stress. Photosynthetic efficiency parameters, including chlorophyll fluorescence and stomatal conductance, were determined using non-invasive methods, while pigments were quantified spectrophotometrically. Non-structural c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Moloi and van der Merwe [6] revealed that reductions in edamame yield under drought stress were associated with the increased production of reactive oxygen species (ROS), which ultimately increased lipid peroxidation. Hlahla et al [7] further associated such reductions in edamame yield with disruptions in the photosynthetic capacity under drought stress.…”
Section: Introductionmentioning
confidence: 99%
“…Moloi and van der Merwe [6] revealed that reductions in edamame yield under drought stress were associated with the increased production of reactive oxygen species (ROS), which ultimately increased lipid peroxidation. Hlahla et al [7] further associated such reductions in edamame yield with disruptions in the photosynthetic capacity under drought stress.…”
Section: Introductionmentioning
confidence: 99%
“…Harsh environmental conditions negatively influenced the vegetable soybean production [ 32 , 33 , 34 , 35 , 36 ]. In recent years, due to high nutritional benefit, the cultivation area of vegetable soybean had gradually expanded worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…During growth and development, the pattern of carbohydrate allocation in plants is determined by source-sink interactions. This process plays a critical role in regulating carbon (C) assimilation and distribution, which ultimately impacts crop productivity (Hlahla et al, 2022).…”
Section: Regulation Of Source-sink Dynamicsmentioning
confidence: 99%
“…During growth and development, the pattern of carbohydrate allocation in plants is determined by source‐sink interactions. This process plays a critical role in regulating carbon (C) assimilation and distribution, which ultimately impacts crop productivity (Hlahla et al, 2022). Drought stress alters the source‐sink relationship by curbing the source strength, which leads to yield reduction (Desoky et al, 2021).…”
Section: Tolerance Mechanisms‐induced By Ethylene Under Drought Stressmentioning
confidence: 99%